Split Cast Metal Post and Core - Chopra, Devendra; Kumar Singh, Naorem Satish; Nehete, Parag (Journal of Orofacial Research, 2012)
The best plan for success is to begin with the end in mind. It generally is agreed that the successful treatment of a badly broken down tooth with pulpal disease depends not only good endodontic therapy, but also on good prosthetic reconstruction of the tooth after endodontic therapy. The primary purpose of the post is to retain a core that can be used to retain definitive prostheses. A post and core help prevent coronal fractures when the remaining coronal structure is very thin after tooth preparation. When a substantial amount of coronal structure is lost a cast post and core is indicated. In this clinical report the root canal treated left mandibular first molar is restored with split cast metal post and core design using the direct technique for the fabrication of the post and core pattern using the autopolymerizing acrylic resin material and then further casted in the laboratory using the base metal alloy.